Accessory corpus luteum regression during pregnancy I: timing, physiology, and P4 profiles. Issue 6 (15th November 2021) - Monteiro, Pedro L J; Sartori, Roberto; Canavessi, Aurea M O; Melo, Leonardo F; Motta, Jessica C L; Consentini, Carlos E C; Wiltbank, Milo C
Abstract : Inappropriate corpus luteum (CL) regression can produce pregnancy loss. An experimental model was utilized to investigate regression of accessory CL during pregnancy in dairy cows. Cows were bred (day 0) and treated with gonadotrophin-releasing hormone 6 days later to form accessory CL. Transrectal ultrasound (every other days) and blood samples for progesterone (P4; daily) were performed until day 56 of pregnancy. On day 28, 13 cows were confirmed pregnant, and accessory CL were found contralateral ( n = 9) or ipsilateral ( n = 4) to previous ovulation. On day 18, CL biopsy was performed to analyze mRNA expression for interferon-stimulated genes (ISGs). Luteolysis occurred more frequently in cows that had contralateral accessory CL (88.9% (8/9)) than in cows with ipsilateral accessory CL (0% (0/4)). Luteolysis of contralateral accessory CL occurred either earlier (days 19–23; 2/8) or later (days 48–53; 6/8) in pregnancy and occurred rapidly (24 h), based on daily P4. After onset of earlier or later accessory CL regression, circulating P4 decreased by 41.2%. There was no difference in luteal tissue mRNA expression for ISGs on day 18 between accessory and original CL and between CL that subsequently regressed or did not regress. On day 56, an oxytocin challenge dramatically increased prostaglandin F2α metabolite (PGFM) in all cows but produced no pregnancy losses, although cows with previous accessory CL regression had greater PGFM. In summary, ipsilateral accessory CL did not regress during pregnancy, whereas most contralateral CL regressed by 63 days of pregnancy, providing evidence for local mechanisms in regression of accessory CL and protection of CL during pregnancy.